Sex after fascism : memory and morality in twentieth-century Germany - Herzog, Dagmar, 1961- (Princeton University Press, 2005)
"Sex after Fascism fundamentally reconceives central topics in twentieth-century German history. Among other things, it changes the way we understand the immense popular appeal of the Nazi regime and the nature of antisemitism, the role of Christianity in the consolidation of postfascist conservatism in the West, the countercultural rebellions of the 1960s-1970s, as well as the negotiations between government and citizenry under East German communism